Nasal Peak Inspiratory Flow in Healthy and Obstructed Patients: Systematic Review and Meta‐Analysis. (9th May 2020) - Mo, Shirley; Gupta, Sai S.; Stroud, Anna; Strazdins, Erika; Hamizan, Aneeza W.; Rimmer, Janet; Alvarado, Raquel; Kalish, Larry; Harvey, Richard J.
Abstract : Objectives: Nasal peak inspiratory flow (NPIF) is a practical and affordable tool that measures maximum inspiratory flow rate through both nostrils. Although NPIF values for healthy controls and patients appear to differ considerably, a generally expected value for populations with and without nasal obstruction has yet to be established. The aim of this systematic review and meta‐analysis was to determine the mean NPIF value in populations with and without nasal obstruction. Methods: Medline (1946–) and Embase (1947–) were searched until July 1, 2017. A search strategy was used to identify studies that reported NPIF values for defined healthy or disease states. All studies providing original data were included. The study population was defined as having either normal nasal breathing or nasal obstruction. A meta‐analysis of the mean data was presented in forest plots, and data were presented as mean (95% confidence interval [CI]). Results: The search yielded 1, 526 studies, of which 29 were included. The included studies involved 1, 634 subjects with normal nasal breathing and 817 subjects with nasal obstruction. The mean NPIF value for populations with normal nasal breathing was 138.4 (95% CI: 127.9‐148.8) L/min. The mean value for populations with nasal obstruction was 97.5 (95% CI: 86.1‐108.8) L/min. Conclusions: Current evidence confirms a difference between mean NPIF values of populations with and without nasal obstruction. The mean value of subjects with no nasal obstruction is 138.4 L/min, and the mean value of nasally obstructed populations is 97.5 L/min. Prospective studies adopting a standardized procedure are required to further assess normative NPIF values. Laryngoscope, 131:260–267, 2021